Nataría Portuguesa: a business plan for Argentina - Câmara, Maria da Pureza Correia Guedes Iinfante da (2018)
This thesis consists on a Business Plan for the Portuguese custard tarts in Argentina. Nataría Portuguesa is already being implemented and so, this project will serve as a support for the same. After developing the literature review, a description of the business idea was made, followed by a macro-environmental analysis of the country and an analysis of the baked industry specifically. Afterwards, the Business Model Canvas was applied to connect the key elements of the business. The brand positioning was defined to reach target consumers and a communication plan was described. In the end, a financial contextualization was also conducted.